Moral Message in the Lyrics of Nadin Amizah's Song “Sorai”: A Semiotic Analysis by Roland Barthes - Firman Baehaqi; Khaerudin Imawan (Salus Publica: Journal of Community Service, 2026)
Music often serves as a space for humans to express and interpret emotional experiences that are difficult to express directly. The song “Sorai” by Nadin Amizah presents poetic and symbolic lyrics that open up opportunities for various interpretations, particularly regarding the meaning of relationships, separation, and sincerity. This study aims to reveal the moral message contained in the lyrics of “Sorai” through Roland Barthes' semiotic approach. This study uses an interpretive qualitative method, with data obtained through analysis of the song lyrics, literature study, and interviews with five fans selected purposively. The analysis was conducted by tracing the denotative, connotative, and mythical meanings to understand how the signs in the lyrics form a moral message. The results show that “Sorai” represents human relationships as a process of mutual help and mutual healing, without demands for ownership or continuity. This song constructs the meaning that separation is not a failure, but rather a part of emotional maturity that can be accepted with sincerity. These findings confirm that music not only functions as entertainment, but also as a medium of communication that conveys human values reflectively.